A RESSURREIÇÃO CORPÓREA: O DISCURSO IDENTITÁRIO EM PAULO (I CORINTIOS 15: 35-49) - Aleixo, ângela Maria Pereira (2014)
This dissertation focuses on the discourse of the corporeal resurrection as an identitary in Paul, from the text of 1 Corinthians 15:35-49 where the apostle develops and argues his eschatological thoughts about this theme. Our goal is to understand how this thought was developed and consider the arguments within this new theological vision of the theme. Methodologically, an exegesis of the text of 1 Corinthians 15:35-49 is made in order to discourse with the thematic concept of Dn 12:1-3 and with the skeptical ideology present in Corinth. Based on the main authors Nickelsburg, Wright and Lehtipuu, we have as main considerations that the corporeal resurrection in Daniel 12:1-3 is universal, collective and taken as an act of justice. In skeptical philosophy the ideology is that of relativism. In Paul, resurrection is personal and comprehends the individual as a whole.